Alteration of Peripheral Resistin and the Severity of Acute Pancreatitis: A Meta-Analysis - Yang, Jianhua; Liu, Mengyao; Wang, Shu; Gan, Yuanxiu; Chen, Xiangyu; Tao, Yang; Gao, Junwei (Frontiers in Medicine, 2022)
Introduction: Resistin is a small secretory adipokine which is implicated to obesity and associated diseases. Recently, plenty of research papers have been conducted to explore the association between peripheral resistin and the severity of acute pancreatitis (AP). However, the results were controversial. In this study, we aimed to confirm the effect of peripheral resistin and the development of acute pancreatitis. Methods: A comprehensive online search was performed using the PubMed, Embase, Web of Science, CNKI, and Wanfang databases up through January 20, 2022. The retrieved records and their references were screened to identify additional studies. Data were extracted to calculate the pooled Hedges’ g and its 95% confidence interval, which were selected to assess peripheral resistin levels and the severity of acute pancreatitis. Subgroup analyses, sensitivity analyses, meta-regression, and publication bias tests were also undertaken based on obtained information. Results: A total of eleven studies with 892 acute pancreatitis patients were enrolled in the study. Peripheral resistin levels were significantly increased in severe acute pancreatitis compared with mild acute pancreatitis (Hedges’ g = 2.092, 95% CI: 0.994-3.190, P <0.001). Subgroup analyses based on sample types and ethnicity also showed similar results. A single study did not affect our results, which was verified by sensitivity analysis. Meta-regression analyses revealed that age, gender of the included subjects, sample size, and publication year did not moderate effects on the present results. Conclusion: In our study, peripheral resistin levels were significantly elevated in severe AP patients compared with mild AP patients. Abnormal resistin levels may provide us some new insights in predicting the severity of AP.